2015
DOI: 10.1007/s10278-015-9818-0
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Thoracic Digital Tomosynthesis (DTS) for the Identification of Lung Nodules

Abstract: Thoracic computed tomography (CT) is considered the gold standard for detection lung pathology, yet its efficacy as a screening tool in regards to cost and radiation dose continues to evolve. Chest radiography (CXR) remains a useful and ubiquitous tool for detection and characterization of pulmonary pathology, but reduced sensitivity and specificity compared to CT. This prospective, blinded study compares the sensitivity of digital tomosynthesis (DTS), to that of CT and CXR for the identification and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 14 publications
3
10
0
Order By: Relevance
“…24,25,27 Also, several studies demonstrated the effective dose of each modality for standard patient in each study protocol, [9][10][11][12]21 and we found that the radiation dose for DTS was approximately twice that for chest radiography and DTS required a much smaller radiation dose in comparison with CT.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…24,25,27 Also, several studies demonstrated the effective dose of each modality for standard patient in each study protocol, [9][10][11][12]21 and we found that the radiation dose for DTS was approximately twice that for chest radiography and DTS required a much smaller radiation dose in comparison with CT.…”
Section: Discussionsupporting
confidence: 52%
“…In our meta-analysis, some studies which used CT as the reference standard did not suggest the truenegative number, because they demonstrated only the true-positive number of nodules detected with DTS and chest radiography among nodules detected with CT. 13,22,23 In other studies, sensitivity was estimated on a per-lesion basis, but specificity was exclusively estimated on per-patient basis. 9,11,21,27 Thus, we inevitably analyzed the detection rate from lesion-based data because we considered those information could be significant for evaluating the diagnostic value for the detection of pulmonary nodule despite definite limitations. The meta-analysis for lesion-based studies was performed using two groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of false-positive findings were due to normal lung structures, such as bronchioles. The position of the nodules in the lobes reflects the non-easy association of nodules to lung lobes more than an actual difference between the two methodologies and the values we found are comparable to those of the literature [28]. Besides, there is a real difficulty in describing nodules that are adjacent to the thoracic wall in DTS with respect to CT, because of the spill-in of higher density region into the lung.…”
Section: Discussionsupporting
confidence: 88%
“…In the Table 1 SOS study, we showed that 6.5 × 10 −1 % of subjects had lung cancer, to be compared to a nearly 500 times lower risk of REID (0.3 × 10 −3 %) for the same pathology, suggesting that the screening procedure, even if expose the subjects to radiation, is advantageous. All the published studies [14,16,[26][27][28] on DTS report the sensitivity of DTS using CT as a reference, defining sensitivity as the ratio of number of nodules detected by DTS and CT. This is a direct consequence of the design of these studies that were conceived to test DTS on a population of subjects that already performed, for different reasons, a CT scan.…”
Section: Discussionmentioning
confidence: 99%